VD_FINDINFO Jug / 2019 / 357 vom 4. November 2019 - VD Tribunal cantonal (2019)
DROIT D'AUTEUR ET DROITS VOISINS, DROIT DE LA PROPRIÉTÉ INTELLECTUELLE, TARIFEN GÉNÉRAL, PRESCRIPTION | 102 CO, 104 CO, 127 CO, 128 CO, 19 LDA, 20 LDA, 51 LDA, 59 LDA, 59 CPC (CH), 60 CPC (CH)